Water quality assessment of the Bagmati river using biotic index - Pandey, Manoj Kumar (Nepalese Journal of Engineering, 2005)
This paper analyses the quality of the Bagmati River using Extended Biotic Index (EBI) method. The macroinvertebrates population was studied at seven locations along the Bagmati River from Sundarijal to Khokana. Based on the EBI value the most polluted location is station V at Sundarighat just upstream of the confluence of Bagmati and Bishnumati River. The biological quality analysis reveals that the middle part of the river between the Sundarijal and Khokana is highly polluted. The study has tried to depict the importance of biological parameters to assess the quality of the river system. Keywords: Bagmati River, Extended Biotic Index, Macroinvertebrates Nepalese Journal of Engineering Vol.1(1) 2005 pp.70-75